Assessing Employee Engagement Level in FnB Service Industry: Case Study PT XYZ Indonesia - Azzahra, Hasna Rahmi; Putranto, Nur Arief Rahmatsyah (Journal Integration of Social Studies and Business Development, 2023)
The food and beverage service industry has grown rapidly in Bandung region over the past ten years. The industry itself is a customer-focused industry. In this regard, employees are a valuable asset for a company. Therefore, a company needs to have employees engaged in their workplace. The ability of engaged employees to assist the business in numerous ways, particularly concerning sustainability, has also been demonstrated. As a holding company founded in 2017, PT XYZ manages six cafe branches in Bandung and Cimahi. During an interview, the human resources manager stated that in 2022, the turnover rate increased by 4% compared to the previous year in 2021, when there were no resignations at all. Apart from that, many employees are content to stay in the company. In addition, the company had never conducted an employee engagement assessment to measure employee engagement to the company since it did not have the tools while measuring employee engagement is considered important for improving its overall performance. The researcher chose the Aon Hewitt employee engagement model to measure employee engagement because it can classify and identify facets of employee engagement consisting of “say, stay, strive.” The model can also determine which drivers influence an employee’s engagement or disengagement. A Likert scale-based questionnaire from 1 to 6 was distributed to 122 employees as part of the research’s quantitative methodology. The study’s findings indicate that 81% of PT XYZ employees are highly engaged, with an average of 80% of employees representing “say, stay, strive.” In addition, diversity and inclusion is a driver that influences employees to be engaged, with a value of 92.37, while the last-ranked driver is a risk, with a value of 64.69.